Tumour location determined by preoperative MRI is an independent predictor for positive surgical margin status after Retzius‐sparing robot‐assisted radical prostatectomy. (17th April 2020) - Li, Youjian; Fu, Yao; Li, Weijian; Xu, Linfeng; Zhang, Qing; Gao, Jie; Li, Danyan; Li, Xiaogong; Qiu, Xuefeng; Guo, Hongqian
Abstract : Objective: To investigate the influence of tumour location zone on positive surgical margin (PSM) status after Retzius‐sparing robot‐assisted radical prostatectomy (RS‐RARP). Materials and Methods: A total of 203 consecutive patients with prostate cancer (PCa) who underwent RS‐RARP at our centre were divided into three cohorts according to the tumour zonal origin described on preoperative magnetic resonance imaging (MRI). Clinical and pathological characteristics were compared among the three groups. The associations of clinicopathological variables with PSM status after RS‐RARP were also evaluated. Results: The rates of PSM in patients with transition zone (TZ) and mixed origin tumours were significantly higher than in patients with peripheral zone tumours ( P < 0.01). Of the PSMs in patients with TZ and mixed origin cancers, 42.0% and 40.9%, respectively, were located at the anterior part of the gland. On multivariate analysis, presence of a TZ tumour was significantly associated with a higher PSM rate after RS‐RARP ( P < 0.01). Sub‐analysis showed that high‐risk patients with TZ tumours had a higher risk of PSM after RS‐RARP ( P < 0.01). Conclusion: Presence of a TZ tumour is an independent risk factor for PSMs after RS‐RARP. Preoperative identification of TZ tumours might aid surgical planning for the Retzius‐sparing technique, especially in high‐risk patients.